General aviation aircraft design applied methods and procedures - Gudmundsson, Snorri (Butterworth-Heinemann, 2021)
General Aviation Aircraft Design, Second Edition, continues to be the engineer's best source for answers to realistic aircraft design questions. The book has been expanded to provide design guidance for additional classes of aircraft, including seaplanes, biplanes, UAS, high-speed business jets, and electric airplanes. In addition to conventional powerplants, design guidance for battery systems, electric motors, and complete electric powertrains is offered. The second edition contains new chapters: Thrust Modeling for Gas Turbines Longitudinal Stability and Control Lateral and Directional Stability and Control These new chapters offer multiple practical methods to simplify the estimation of stability derivatives and introduce hinge moments and basic control system design. Furthermore, all chapters have been reorganized and feature updated material with additional analysis methods. This edition also provides an introduction to design optimization using a wing optimization as an example for the beginner. Written by an engineer with more than 25 years of design experience, professional engineers, aircraft designers, aerodynamicists, structural analysts, performance analysts, researchers, and aerospace engineering students will value the book as the classic go-to for aircraft design.